Intolerância religiosa em ambiente de trabalho: um estudo sobre seus mecanismos, implicações e soluções. - Ferreira, Diogo Gonçalves (2017)
This master thesis will investigate how religious intolerance develops in the workplace, which are the consequences for practitioners and victims of such acts, and how Brazilian Law and the State deal with it. From a historical analysis of the cases of religious intolerance in Brazil in the Colony, Empire and Republic, through the formation of the Laic State and as the current Brazilian legislation started to treat the theme, we will try to construct a research on a subject few studied in the country. In this paper we will present an analysis of the constitutional guarantees which governing the labor laws about religious intolerance, raising statistics on religious intolerance in the workplace, to provide new and updated sources of knowledge about the subject to researchers in the area, as well as to the general population. In this way, it will be possible to better conceptualize what is an act of religious intolerance, the consequences of this practice are in a workplace, and whether such rights regarding freedom of belief, guaranteed by the Constitution, are being protected, or not, in the daily work relations.